Diagonal agility test innovation in gymnastic performance for children: A construct of the content validity and reability approach - Budiarti, R.; Siswantoyo; Sukamti, E. R.; Fajar Sriwahyuniati, C.; Miftachurochmah, Y.; Fitri, M. (Sport Science - International Scientific Journal of Kinesiology, 2022)
Background: The agility test is important in identifying and developing talent in gymnastics. Purpose: This study aimed to test the content validity and reliability of the diagonal agility test on junior gymnasts. Design/ methodology/approach: The research used both qualitative and quantitative approaches. Data collection was carried out using the Delphi technique involving seven experts. Questionnaires with a scale of 1-5 (very relevant, relevant, quite relevant, less relevant, and irrelevant) were used as instruments. The data was analysed using Aiken`s formula to test content validity and Cronbach`s alpha and intraclass correlation coefficients (ICC) to test the reliability between raters from the diagonal agility test. Result: The findings showed that the Aiken`s coefficient value of all aspects was above 0.71; aspect 1 showed the Aiken`s V coefficient value of 0.750, aspect 2 showed the Aiken`s V coefficient value of 0.750, aspect 3 showed Aiken`s V coefficient value of 0.821, aspect 4 showed the Aiken`s V coefficient value of 1.000, aspect 5 showed the Aiken`s V coefficient value of 0.750, and aspect 6 showed the Aiken`s V coefficient value of 0.857. Therefore, it can be concluded that all items were valid. In addition, Cronbach`s alpha value of 0.880 and ICC of 0.880 was also obtained with a consistency of 0.512 for each rater, suggesting that the instrument was very reliable. Conclusion: Gymnastics` agility measurement test for children has good validity and reliability, so this instrument can be used to measure the agility ability of junior gymnasts. For future research, testing the effectiveness and design of assessment norms is recommended.